MORFOMETRIC ANALYSIS OF MANGROVE CRAB (Scylla serrata) IN TANJUNG REJO VILLAGE, PERCUT SEI TUAN DISTRICT, DELI SERDANG REGENCY, NORTH SUMATERA - Rifqah Amalia; Puji Prastowo (Universitas Negeri Medan, 2022)
This study aims to determine the character that contributes the most to the body weight of mud crab (Scylla serrata) and the morphometric differences between male and female mangrove crabs (Scylla serrata). The research was carried out in Tanjung Rejo Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra from March to April 2022. This research is quantitative descriptive with explorative methods, namely direct sample collection or Hand sorting. The morphometric parameters observed were carapace width, carapace length, carapace height, optical groove widths, chela length, chela height and deep length. The analysis used is multiple linear regression with stepwise method and t test. The results of the study showed that the morphometric characters that contributed the most to body weight in male mud crabs were the length of the right chela (93%) and carapace length (94.1%), while in female mud crabs, carapace height (87%) and carapace width (91%) and there is a very significant difference between male and female mud crab morphometrics on the characters of optical groove widths, right chela length, right chela height, right chela deep length, left chela length, and chela height. on the left and deep length on the left. Meanwhile, significant characters were found in carapace width and carapace height. For carapace length characters showed no significant difference.